Excess mortality in Poland during the first and second wave of the COVID-19 pandemic in 2020 - Małgorzata Pikala; Małgorzata Krzywicka; Monika Burzyńska (Frontiers Media S.A., 2022)
PurposeThe aim of the study was to analyse excess deaths by major causes of death and associated changes in the mortality pattern of the Polish population in 2020 due to the impact of the COVID-19 pandemic.MethodsThe study used data on all deaths in Poland which occurred between 2010 and 2020 (N = 3,912,237). 10-year mortality trends for 2010-2019 were determined. An analysis of time trends has been carried out with joinpoint models and Joinpoint Regression Program. Based on the determined regression models, the number of deaths expected in 2020 and the number of excess deaths due to selected causes were calculated.ResultsThe crude death rates of all-cause deaths increased from 2000 to 2019 at an average annual rate of 1% (p = 0.0007). The determined regression model revealed that the number of deaths in 2020 should have been 413,318 (95% CI: 411,252 to 415,385). In reality, 477,355 people died in Poland that year. The number of excess deaths was therefore 64,037 (15.5%). According to data from Statistics Poland the number of COVID-19-related deaths was 40,028, the number of non-COVID-19 deaths was 24,009. The largest percentage increase over the expected number of deaths was observed for suicide (12.5%), mental and behavioral disorders (7.2%) and diseases of circulatory system (5.9%). A lower than expected number of deaths was observed for malignant neoplasms (−3.2%) and transport accidents (−0.1%).ConclusionThe difference between expected and observed non-COVID-19 deaths in 2020 indicates a need for further analysis of the causes of excess mortality.